Artistic Representations of Suffering: Rights, Resistance, and Remembrance - Celinscak, Mark; Hutt, Curtis (Rowman & Littlefield Publishers, 2021)
Artistic expression frequently engages with the question of suffering. In so doing, it confronts the gravity and complexity of the human condition. This volume investigates the relationship between art and suffering. In short, the contributors to this volume collectively demonstrate that suffering is an undisputed and shareable motivating experience. This collection features original essays that focus on the subject of art and suffering, including topics such as the representation of violence and the intersections of art and human rights. Some of the key questions explored are as follows: How has suffering motivated artists around the world? How have artists used their platforms to call attention to human rights abuses? How can suffering be incorporated responsibly and ethically in works of art? What role does art play in the struggle against violations of human dignity and the promotion of building a more equitable world? Each essay is complemented by full-color reproductions of artistic works that illustrate the concepts being discussed, including a graphic essay on the topic of “comfort women.”